Design and construction of a LiBr–water absorption machine - Florides, Georgios A.; Kalogirou, Soteris A.; Tassou, Savvas A.; Wrobel, L. C. (My University, 2003)
The objective of this paper is to present a method to evaluate the characteristics and performance of a single stage lithium bromide (LiBr)–water absorption machine. The necessary heat and mass transfer equations and appropriate equations describing the properties of the working fluids are specified. These equations are employed in a computer program, and a sensitivity analysis is performed. The difference between the absorber LiBr inlet and outlet percentage ratio, the coefficient of performance of the unit in relation to the generator temperature, the efficiency of the unit in relation to the solution heat exchanger area and the solution strength effectiveness in relation to the absorber solution outlet temperature are examined. Information on designing the heat exchangers of the LiBr–water absorption unit are also presented. Single pass, vertical tube heat exchangers have been used for the absorber and for the evaporator. The solution heat exchanger was designed as a single pass annular heat exchanger. The condenser and the generator were designed using horizontal tube heat exchangers. The calculated theoretical values are compared to experimental results derived for a small unit with a nominal capacity of 1 kW. Finally, a cost analysis for a domestic size absorber cooler is presented.
Keywords: Absorption cooling; Lithium bromide; Sensitivity analysis; Heat exchangers